Aplikasi Game 2D berbasis Andorid dengan Logika Fuzzy pada NPC (Non-Player Character): Android-based 2D Game Application with Fuzzy Logic on NPC (Non-Player Character) - Ibzani Ilham Shagianto; Giri Wahyu Wiriasto; Djul Fikri Budiman; Misbahuddin; Ni Made Seniari (Depertment of Electrical Engineering University of Mataram, 2023)
Various games emerge with different types, platforms, qualities, and popularity. This is due to the integration of many tools with the Android Operating System. Therefore, the main objective of this research is to create a game in the form of an application with Artificial Intelligence for Non-Player Characters (NPC). The implementation of Fuzzy Logic on the NPC aims to enable the NPC to make Decision Making (DM) for dynamic movements, attacking the character played by the human player with the intention of inflicting damage through forward, backward, and attacking movements, gradually reducing the health point (HP) parameter until it is depleted, thus allowing the NPC to win the game. Similarly, the human player will also attack the NPC with forward, backward, jumping, and attacking movements. We named this mobile game